Effects of woven fabric embedment on thin film composite membranes for osmotically driven membrane processes (ODMPs) - Teo, Shino Yu Qin (Nanyang Technological University, 2024)
Osmotically driven membrane processes (ODMPs) have drawn a lot of attention in recent years due to their potential applications in water purification, desalination and energy generation. ODMPs are encompassed by Forward Osmosis(FO), Pressure Assisted Osmosis (PAO) and Pressure Retarded Osmosis (PRO). Among these, PRO is known for its renewable energy generation through osmotic gradients in recent years, with thin film composite membrane (TFC) playing a crucial role in its efficiency. While the technology itself shows potential, further advancement in ODMP membrane development is necessary to fully harness its power production capabilities. Specifically, PRO membranes must possess high mechanical strength to withstand the elevated hydraulic pressure experienced on the draw side of the membrane.